Political Power, Desegregation, and Employment of Black Schoolteachers - Freeman, Richard B. (Journal of Political Economy, 1977)
[This paper examines the impact of de jure desegregation on education in the South and of increased black voting power on the demand for black schoolteachers in the United States. Because changes in the black share of voters in the post-World War II South are due largely to "exogenous" national laws (the Voting Rights Act of 1965, in particular), the paper provides a unique test of the impact of changes in political power on public decision making. The main finding is that increased black voting power appears to have raised demand for black school-teachers in the 1960s. There is additional suggestive evidence that black voting power operated in part through election of black officials. The increase in demand due to the changes in voting offset most of the reduction in demand due to desegregation of schooling in the South, averting the potential dire effects of desegregated education on employment of black teachers. Instead of declining, relative employment of blacks in teaching was maintained, and relative incomes rose in the 1950s and 1960s. These results are consistent with broad "governmental discrimination" hypothesis that much of the economic progress or retrogression of blacks in the United States is explicable in terms of black political power and resultant governmental activity.]